METHODOLOGICAL QUESTIONS ON IMPROVEMENT OF STATE REGULATION OF DEVELOPMENT OF THE TRANSPORT BRANCH - Ilya Tkachev (Вестник Северо-Кавказского федерального университета)
The article is devoted to problem of improving of state regulation of transport branch. The article lists the objects, subjects, general aims of state regulation of transport; the generalized classification of methods of regulation, including the 31 methods; outlines the basic algorithm of improvement of state regulation of functioning and development of transport branch, including the 10 blocs; describes each bloc of this algorithm; outlines the algorithm of selection and justification of concrete methods of state regulation offunctioning and development of transport branch.